The moderating role of adaptability in enhancing competitive advantage through market insight, business strategy, and innovation - Baskara, Muhamad; Madiawati, Putu Nina; Syahputra, Syahputra (CV. Syntax Corporation Indonesia, 2025)
In the increasingly competitive real estate sector, firms are required to optimize Market Insight, Business Strategy, and Innovation while simultaneously adapting to dynamic conditions in order to sustain Competitive Advantage. This study investigates the structural relationship between these strategic drivers and examines how Innovation mediates and Adaptability moderates their impact on Competitive Advantage. A quantitative approach was adopted using Structural Equation Modeling based on the Partial Least Squares (SEM-PLS) technique, with data collected from 185 respondents within the Indonesian real estate industry. The results demonstrate that both Market Insight and Business Strategy significantly influence Innovation and Competitive Advantage, with Innovation serving as a partial mediator. Furthermore, Adaptability strengthens the positive effect of Innovation on Competitive Advantage, highlighting the importance of organizational responsiveness in turbulent environments. The findings indicate that firms integrating market-oriented strategies with innovation and adaptive capabilities tend to outperform competitors in sustaining long-term advantage. Theoretically, this research extends existing frameworks on dynamic capability and competitive strategy by emphasizing the contingent role of Adaptability. Practically, it provides guidance for decision-makers in formulating data-driven and flexible business strategies. Limitations of the study include its industry-specific context and the cross-sectional nature of the data. Future research is recommended to apply the proposed model across multiple sectors and to incorporate additional constructs such as digital transformation, customer engagement, and organizational resilience in order to broaden the theoretical contribution.